Five Species of Wild Freshwater Sport Fish in Wisconsin, USA, Reveal Highly Diverse Viromes - Charlotte E. Ford; Christopher D. Dunn; Eric M. Leis; Whitney A. Thiel; Tony L. Goldberg (Pathogens, 2024)
Studies of marine fish have revealed distant relatives of viruses important to global fish and animal health, but few such studies exist for freshwater fish. To investigate whether freshwater fish also host such viruses, we characterized the viromes of five wild species of freshwater fish in Wisconsin, USA: bluegill (Lepomis macrochirus), brown trout (Salmo trutta), lake sturgeon (Acipenser fulvescens), northern pike (Esox lucius), and walleye (Sander vitreus). We analyzed 103 blood serum samples collected during a state-wide survey from 2016 to 2020 and used a metagenomic approach for virus detection to identify known and previously uncharacterized virus sequences. We then characterized viruses phylogenetically and quantified prevalence, richness, and relative abundance for each virus. Within these viromes, we identified 19 viruses from 11 viral families: Amnoonviridae, Circoviridae, Coronaviridae, Hepadnaviridae, Peribunyaviridae, Picobirnaviridae, Picornaviridae, Matonaviridae, Narnaviridae, Nudnaviridae, and Spinareoviridae, 17 of which were previously undescribed. Among these viruses was the first fish-associated coronavirus from the Gammacoronavirus genus, which was present in 11/15 (73%) of S. vitreus. These results demonstrate that, similar to marine fish, freshwater fish also harbor diverse relatives of viruses important to the health of fish and other animals, although it currently remains unknown what effect, if any, the viruses we identified may have on fish health.